2014
DOI: 10.1039/c4tc01427h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis and tunable luminescence of uniform YPO4·0.8H2O and YPO4·0.8H2O : Tb3+/Eu3+ nanocrystals by a facile approach

Abstract: The emission spectra of Y0.96−xPO4·0.8H2O : 0.04Tb3+, xEu3+ (x = 0–0.18) nanocrystals could result in tunable emission with self-activated luminescence and rare earth-doping emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 61 publications
1
14
0
1
Order By: Relevance
“…2,5 Many research groups have reported, in the last decade, on the doping of YPO 4 , LaPO 4 , CePO 4 , and GdPO 4 nanoparticles with ions of the f-elements for optoelectronic as well as biotechnological applications. [6][7][8][9][10][11][12][13] However, very few reports have been found in the literature which describe the synthesis of LuPO 4 particles. Gao et al 14 reported the synthesis of uniform LuPO 4 hollow spheres using a two-step urea-based process which rendered particles with a diameter of around 300 nm, well above the size of nanometer-scale materials.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 Many research groups have reported, in the last decade, on the doping of YPO 4 , LaPO 4 , CePO 4 , and GdPO 4 nanoparticles with ions of the f-elements for optoelectronic as well as biotechnological applications. [6][7][8][9][10][11][12][13] However, very few reports have been found in the literature which describe the synthesis of LuPO 4 particles. Gao et al 14 reported the synthesis of uniform LuPO 4 hollow spheres using a two-step urea-based process which rendered particles with a diameter of around 300 nm, well above the size of nanometer-scale materials.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Actually, citrate is oen used as a structure-directing agent to control the nucleation, growth and alignment of REPO 4 crystals. 24,25 In order to achieve the phase transformation of REPO 4 compounds at low temperature, the organic ligand-induce might be a feasible method.…”
Section: àmentioning
confidence: 99%
“…Europium Eu 3+ ion is utilized as a red‐emitting actuator in commercial phosphors, this is attributed to the 5 D 0 → 7 F J (J = 1–6) transitions in the red spectral region. [ 17,19 ] Graca et al . [ 20 ] described the luminescence properties of the EuNbO 4 and its intense red emission and the formation of multiple Eu 3+ optical active centres.…”
Section: Introductionmentioning
confidence: 99%
“…7 F J (J = 1-6) transitions in the red spectral region. [17,19] Graca et al [20] described the luminescence properties of the EuNbO 4 and its intense red emission and the formation of multiple Eu 3+ optical active centres. Intra-4f shell downconversion ( 5 D 0 !…”
mentioning
confidence: 99%